Sommige metodes en toepassings van kwadratiese programmering - De Kock, H. C.(Hendrik Cornelis) (Stellenbosch : Stellenbosch University, 2012)
Proefskrif (M. Sc.) -- Universiteit van Stellenbosch, 1968.